A Case Report on Thyroid Metastasis from Primary Breast Cancer: An Unusual Secondary Site Demonstrated by FDG PET/CT scan (Pulse, 2025)
Metastasis to the thyroid gland from non-thyroid sites is an uncommon clinical presentation despite its rich blood supply. On the other hand, breast cancer frequently metastasizes to the bones, lungs, brain and liver, rather than thyroid gland which represents a rare target site for secondary disease. Metastasis to thyroid is clinically rare, with an incidence of 0.36% in all thyroid malignant tumors. We report the case of a 62-year-old woman with HER2-positive breast cancer, in whom lung and liver metastases were detected at initial diagnosis. Nearly four years later, follow-up imaging revealed a thyroid nodule, and ultrasound-guided core biopsy confirmed metastatic carcinoma consistent with the breast primary. With this breast cancer case with thyroid metastasis, we suggest that physicians involved in the follow-up care of breast cancer patients should consider a differential diagnosis of secondary thyroid malignancy when incidental lesions are diagnosed during radiological evaluations or local symptoms affect the cervical region, even many years after the diagnosis of primary cancer.Pulse Vol.17, 2025 P: 33-36